Chromosome Structural Alteration an Unusual Abnormality Characterizing Human Neoplasia - Movafagh, Abolfazl; Hashemi, Mehrdad; Heidary Pour, Atefeh; Zare-Abdollahi, Davood; Emamalizadeh, Babak; Shahvaisizadeh, Farhad; Mansouri, Neda; Heidari, Mohammad Hassan; Tonekaboni, Hassan (Novelty in Biomedicine, 2016)
Background and Aim: Ring chromosomes are rare cytogenetic abnormalities that occur in less than 10% of hematopoietic malignancies. They are rare in blood disorder. The present review has focused on the ring chromosome associated with oncology malignancies. Materials and Methods: By reviewing the web-based search for all English scientific peer review articles published, was initiated using Medline/PubMed, Mitelman database (http://cgap.nci.nih.gov/Chromosomes/Mitelman), and other pertinent references on websites about ring chromosomes in Oncology. The software program as End Note was used to handle the proper references for instruction to author. Karyotype descriptions were cited according to ISCN. Conclusion: Ring chromosomes are rare chromosomal aberrations, almost many times are of de novo origin, presenting a different phenotype regarding the loss of genetic material. The karyotype represents the main analysis for detection of ring chromosomes, but other molecular technics are necessary for complete characterization. The information of this review article adds to the spectrum of both morphology and genetic rearrangements in the field of oncology malignancies.